1996
DOI: 10.3109/00365599609181317
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Haemodialysis Session on Plasma Beta-Endorphin, ACTH and Cortisol in Patients with End-Stage Renal Disease

Abstract: The effect of a regular haemodialysis session on the plasma concentrations of beta-endorphin, ACTH and cortisol was investigated in 14 patients with end-stage renal disease and 20 healthy controls. Blood for analysis of beta-endorphin, ACTH and cortisol was sampled before and immediately after haemodialysis. In four patients the dialysate was studied for presence of these hormones, but showed no specific activity. The predialysis beta-endorphin, ACTH and cortisol levels did not differ significantly from the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
2
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 22 publications
0
18
2
1
Order By: Relevance
“…Although most studies have demonstrated HPA axis integrity in patients with renal failure (20,33), our findings revealed a greater activation of the HPA axis and a high level of stress. Therefore, it is necessary to emphasize that chronic or prolonged stress responses may cause several disease states (45) and contribute to important sleep pattern changes (42).…”
Section: Discussioncontrasting
confidence: 55%
“…Although most studies have demonstrated HPA axis integrity in patients with renal failure (20,33), our findings revealed a greater activation of the HPA axis and a high level of stress. Therefore, it is necessary to emphasize that chronic or prolonged stress responses may cause several disease states (45) and contribute to important sleep pattern changes (42).…”
Section: Discussioncontrasting
confidence: 55%
“…Glucocorticoids are described to increase ZAG secretion [35], [36]. And cortisol level has been shown to be increased by hemodialysis session [37] suggesting that glucocorticoids could enhance ZAG secretion and contribute to the perdialytic increase in plasma ZAG concentration. In contrast, inflammatory cytokines such as TNF-alpha were shown to decreased ZAG secretion [38][40].…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, assessing 24-h urinary-free cortisol excretion largely depends on how precisely an individual patient collects urine and on her/his renal function. Plasma binding protein concentrations and dexamethasone clearance can be significantly altered with decreased renal function [143,196,197]. Recent studies have [195], with permission from The Endocrine Society) shown a disrupted circadian cortisol rhythm in patients with ESRD, whereas previous studies showed normal rhythms [197][198][199][200].…”
Section: Diagnosismentioning
confidence: 99%